George Bryan papers - Bryan, George, 1731-1791.
Memoranda of events concerning Indian wars, Society of Friends, and local events in Philadelphia, entered in the back of "The Gentleman's Almanack" (1760); and ALS (28 March 1786; Philadelphia) from Bryan to John Nicholson concerning public funding for a hospital in Philadelphia, Pa.
Public official and jurist from Pennsylvania.
Collection material in English.
Keywords: Nicholson, John, -- 1757-1800 -- Correspondence; Hospitals -- Pennsylvania -- Philadelphia; Indians of North America -- Wars -- 1750-1815.; Indians of North America -- Wars -- Pennsylvania; Society of Friends -- Pennsylvania; Pennsylvania -- History -- Colonial period, ca. 1600-1775.; Philadelphia (Pa.) -- History; Jurists; Public officials -- Pennsylvania